THE DYNAMICS OF POLITICAL IDENTITY IN THE DIGITAL ERA: THE ROLE OF SOCIAL MEDIA, POLARIZATION, AND CHALLENGES TO DEMOCRACY - Karmila, Leti; Yuningsih, Ani (TOPLAMA, 2025)
In this study, the researcher explores the role of social media in constructing political identity in the digital era. The research analyzes how social media platforms facilitate the expression and formation of individual and group political identities and how this influences the dynamics of communication and social interaction within the political realm.  The main focus of this study is on two aspects:  First, the changing dynamics of political communication and interaction. Social media provides new spaces for political expression but, on the other hand, can also facilitate the creation of 'echo chambers' that reinforce political polarization and the spread of disinformation. Second, the impact on democracy: this research examines how social media affects public perception and political decisions, and how these platforms can be used to mobilize political support.  A qualitative approach is used to gain a deep understanding of the impact of social media in the contemporary political context.  The findings of this study highlight the importance of digital literacy as a key to combating disinformation, and polarization,  and maintaining the health of democracy in the digital era.